West Indian Posters and Prints Collection - (:unkn) unknown (My University, 2015)
A print guide to the posters and prints collection held in the West Indiana and Special Collections Division of the Alma Jordan Library.
A print guide to the posters and prints collection held in the West Indiana and Special Collections Division of the Alma Jordan Library.
Keywords: Caribbean Posters.; Caribbean Prints.